Prevalence, patterns, and correlates of physical activity in Nepal: findings from a nationally representative study using the Global Physical Activity Questionnaire (GPAQ) - Zeljko Pedisic; Nipun Shrestha; Paul D. Loprinzi; Suresh Mehata; Shiva Raj Mishra (BMC, 2019)
Abstract Background The promotion of a physically active lifestyle might help address the increasing burden of non-communicable diseases in Nepal. However, there is a lack of nationally representative estimates of physical activity (PA) prevalence in Nepal. The aim of this nationwide cross-sectional study was to determine domain-specific PA levels and the association of socio-demographic and lifestyle characteristics with total PA among Nepalese adults aged 15-69 years. Methods The data were collected using self-administered questionnaires in a nationally representative sample of 4143 adults (66.5% females), comprised of both rural and urban populations in Nepal. PA levels were assessed using the Global Physical Activity Questionnaire (GPAQ). Results Based on self-reported estimates, around 97% (95% confidence interval [CI]: 96-98%) of men and 98% (95% CI: 98-99%) of women were found to meet the recommended levels of PA. Both men and women reported high occupational PA, whilst most participants of both sexes did not report engaging in any leisure-time PA. A multiple regression analysis showed that less self-reported total PA was associated with older age, higher level of education, urban place of residence, never been married, being underweight, and smoking in both sexes and with overweight and obesity in males (p < 0.05 for all). Conclusion According to self-reported estimates, majority of Nepalese men and women are meeting the recommended levels of PA. The total self-reported PA in Nepalese adults is high, because many of them have labour intensive jobs. Although older age, higher level of education, urban place of residence, never been married, being underweight, and smoking in both sexes, as well as overweight and obesity in males were inversely associated with self-reported PA, the overall level of PA in all these groups was very high. Given the high overall self-reported PA found in the current study, promoting more PA in Nepal may not be as important as in some other countries; not even in the population groups for which we found a negative association with PA. Nevertheless, future studies should examine whether a more balanced distribution of occupational and leisure-time PA would promote better health among Nepalese adults.